ANALYSIS OF PHYSICAL ACTIVITY LEVELS, ECONOMIC STATUS AND DEPRESSION SYMPTOMS IN PEOPLE WITH DIABETES MELLITUS IN BANDUNG CITY - Putri Kirey, Anastasya
nsufficient physical activity can be at risk of causing other additional diseases in people with diabetes mellitus, one of which is depression. Apart from that, there is also a lot of evidence that shows a relationship between socio-economic status and the prevalence of diabetes. Therefore, this study aims to find out how much and how the level of physical activity, economic status and depression are related to people with diabetes mellitus in the city of Bandung. The research method used was quantitative descriptive, with Chi-Square test correlation data analysis, totaling 166 subjects who actively participated in prolanis. The results of this study show that the level of physical activity in people with diabetes mellitus in Bandung City tends to be moderate, with low economic status and normal levels of depressive symptoms. Based on the results of data analysis using the Chi-square test, the significance value between physical activity and economic status was 0.272 (P>0.05), meaning that there was no significant relationship. Between physical activity and depressive symptoms, a significance value of 0.273 (P>0.05) was obtained, meaning that there was no significant relationship. Economic status with symptoms of depression obtained a significance value of 0.085 (P>0.05), meaning that there is no significant relationship between economic status and depression in people with diabetes mellitus in the city of Bandung. The conclusion obtained is that among people with diabetes mellitus in the city of Bandung who take part in the chronic diabetes service program, there is no significant relationship between physical activity, economic status and symptoms of depression, because based on facts in the field, sufferers are active in carrying out prolanist activities which can help their healing.